IMPROVING THE EFFICIENCY OF THE HEATING SYSTEM FOR PUBLIC BUILDINGS INFRASTRUCTURE IN THE CONTEXT OF DNURT - Pshinko, O. M.; Kuznetsov, V. H.; Yatsenko, D. K.; Gabrinets, V. O. (Science and Transport Progress, 2021)
Purpose. The paper analyses the possibility and terms of increasing the efficiency of heating and ventilation systems of public buildings at the present stage of development and the specific climatic conditions of Ukraine. The main purpose is to develop specific measures for public buildings, which will lead to a significant reduction in energy costs for heating and air conditioning system. The example is similar system of DNURT compact campus, which is heated with its own autonomous boiler that uses natural gas. Methodology. The statistical heat loss analysis for the last 5 years allows defining the types and calculating the heat loss values for specific conditions. These losses are compared with those in the world practice and based on the comparison and analysis of the current system there are offered the ways to reduce the heat loss values through the use of various technical and organizational methods.The paper also proposes involvement for this purpose of secondary and alternative energy sources. The secondary energy resources include the heat that is emitted by people and that coming out with the air during ventilation of buildings. The renewable sources include solar and geothermal energy. To enhance the heat transfer medium temperature capacity it is proposed to use the heat pumps. Findings. The maximum possible use of the proposed measures and implementation of rational schematic and engineering solutions for heat and hot water supply systems cam reduce the energy loss for heating and hot water by 30-35%. Originality. The paper for the first time proposed the use of new integrated approaches to maintain the desired heat balance in the winter period, as well as the new schematic solutions for heating and ventilation systems, both in winter and in summer, based on the use of heat pumps and secondary energy resources. Practical value. The introduction of the proposed schematic solutions and approaches demand relatively small capital investments and do not require significant reconstruction of already installed systems.